Draft Annual Plan 1986-87 Volume V Irrigation and Flood Control Jammu and Kashmir Government - Planning Commission (Planning Commission, 1985)
Prior to independence, the irrigation to the feeds was provided through Zamindari Kuhl's which was 1.10 lac hectares. It was in 1949 when irrigation Department in the State was created as a separate Organisation.
Jammu and Kashmir Government, Planning and Development Department